Safety and efficacy of probiotic supplementation in 8 types of inflammatory arthritis: A systematic review and meta-analysis of 34 randomized controlled trials - Zeng, Liuting; Deng, Ying; He, Qi; Yang, Kailin; Li, Jun; Xiang, Wang; Liu, Huiping; Zhu, Xiaofei; Chen, Hua (Frontiers in Immunology, 2022)
Objective: To evaluate Safety and efficacy of probiotic supplementation in inflammatory arthritis. Methods: The literature on the treatment of inflammatory arthritis with probiotics has been collected in databases such as CNKI, Pubmed, Cochrane library, Embase, etc. The search time is for them to build the database until May 2022. The included literatures are randomized controlled trials (RCTs) of probiotics in the treatment of hyperuricemia and gout. The Cochrane risk assessment tool was used for quality evaluation, and the Rev Man5.3 software was used for meta-analysis. Results: A total of 37 records were finally included, involving 34 RCTs and 8 types of autoimmune disease (Hyperuricemia and gout, Inflammatory bowel disease arthritis, juvenile idiopathic arthritis [JIA], Osteoarthritis [OA], Osteoporosis and Osteopenia, Psoriasis, rheumatoid arthritis (RA), Spondyloarthritis). RA involved 10 RCTs (632 participants) whose results showed that probiotic intervention reduced CRP. Psoriasis involved 4 RCTs (214 participants) whose results showed that probiotic intervention could reduce PASI scores. Spondyloarthritis involved 2 RCTs (197 participants) whose results showed that probiotic intervention improved symptoms in patients. Osteoporosis and Ostepenia involving 10 RCTs (1156 participants) showed that probiotic intervention improved bone mineral density in patients. Hyperuricemia and gout involving 4 RCTs (294 participants) showed that probiotic intervention improved serum uric acid in patients. OA involving 1 RCTs (433 participants) showed that probiotic intervention improved symptoms in patients. JIA involving 2 RCTs (72 participants) showed that probiotic intervention improved symptoms in patients. Inflammatory bowel disease arthritis involving 1 RCTs (120 participants) showed that probiotic intervention improved symptoms in patients. All of the above RCTs showed that probiotics did not increase the incidence of adverse events. Conclusion: Probiotic supplements may improve Hyperuricemia and gout, Inflammatory bowel disease arthritis, JIA, OA, Osteoporosis and Osteopenia, Psoriasis, RA, Spondyloarthritis. However, more randomized controlled trials are needed in the future to determine the efficacy and optimal dosing design of probiotics.